Tingkat Pengetahuan Mahasiswa dalam Merawat Pasien Jiwa pada Praktik Klinik Keperawatan Jiwa - Prasetyo, Herry; Nugroho, Petrus (Jurnal Keperawatan Soedirman, 2009)
Clinical placement in Psychiatric Hospital is a compulsory for nursing students in the third level during three weeks. This clinical placement is to bridge classroom theory into clinical practice. The objective of this study is to investigate the effect of psychiatric clinical placement towards knowledge about caring for mentally ill. The survey design was used with total sampling 80 nursing student post psychiatric clinical placement. The study found that as a result of clinical placement, around 95% of nursing students had a better knowledge regarding the concept of mental health and mental illness, developing a nursing care plan, medications and providing education towards patients and people in the community. Therefore, a large number of students perceived knowledge of psychiatric patients post a psychiatric clinical placement.